2016
DOI: 10.1007/s12020-016-1069-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes of serum Mir-217 and the correlation with the severity in type 2 diabetes patients with different stages of diabetic kidney disease

Abstract: The aim of this study is to investigate the correlation between serum microRNA-217 and the severity of diabetic kidney disease determined by albuminuria. Four hundred ninety five type 2 diabetes patients were divided into three groups: normoalbuminuric group, microalbuminuric group, and macroalbuminuric group. Serum microRNA-217 levels were validated by real-time polymerase chain reaction. Serum silent information regulator 1, Hypoxia-inducible factor-1α and vascular endothelial growth factor were determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 34 publications
1
28
1
Order By: Relevance
“…Moreover, there was a significant association between Ln (albumin/creatinine ratio) with SIRT1 and miR-217 ( P < 0.05). [18] In another study by Fathy et al ., serum SIRT1 levels were significantly lower in the normoalbuminuric group ( P < 0.05). SIRT1 demonstrated a positive correlation with FBG in normoalbuminuric patients ( P < 0.05) and also a negative correlation with microalbumin in macroalbuminuric patients ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a significant association between Ln (albumin/creatinine ratio) with SIRT1 and miR-217 ( P < 0.05). [18] In another study by Fathy et al ., serum SIRT1 levels were significantly lower in the normoalbuminuric group ( P < 0.05). SIRT1 demonstrated a positive correlation with FBG in normoalbuminuric patients ( P < 0.05) and also a negative correlation with microalbumin in macroalbuminuric patients ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that high glucose inhibited H 2 S production via TLR4 inflammatory pathway in mouse mesangial cells [28]. In addition, the expression of several microRNAs, including miR-192 [29], miR-204 [30], and miR-217 [31], was upregulated by high glucose. According to bioinformatic analysis on the website of “TargetScan,” the predicted target gene of miR-192 and miR-204 is CSE and the predicted target gene of miR-217 is CBS.…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical study showed that miR-217 closely correlates with the severity of DN in patients with T2DM. Serum miR-217 levels positively correlate with the severity of albuminuria and negatively correlate with sirtuin-1 expression in patients with T2DM [19]. In addition, the study by Shao et al showed that miR-217 expression increases in HG-treated rat GMCs.…”
Section: Endogenous Factors Regulate Sirtuin-1 In Diabetic Nephropathymentioning
confidence: 99%